Hypoglycaemia after post-operative oral analgesics administration—a case series - Ahmad, Tashfeen; Muhammad, Zehra Abdul (Journal of the Pakistan Medical Association, 2025)
Analgesics-related hypoglycaemia is rare and is under exploration. The objective of this study is to illustrate the hypoglycaemia in at-risk fracture patients, concurrently treated with post-surgery oral analgesics and concomitant drugs. In a prospective cohort study, 288 adult proximal femoral, ankle, and hindfoot fracture patients, operated on between June 2022 to January 2024 were enrolled. Up to two-weeks post hospital discharge, prescribed analgesics, and adverse events were recorded. Out of these, five cases were observed who developed hypoglycaemia after administration of concomitant analgesic(s), anti-diabetics, and anti-hypertensives. Analgesics prescribed on discharge were Acetaminophen, Tramadol-Acetaminophen, Pregabalin, Celecoxib, etoricoxib, Diclofenac-Misoprostol, Tapentadol, and Ketorolac Tromethamine. With normal dietary intake, the elderly hypertensive and diabetic patients experienced hypoglycaemia (symptoms and/or <70mg/dL glucose level) after analgesics administration. Patients were treated with dextrose, sugar, etc., and after adjustment of analgesics dose were directed to an endocrinologist. It seems that certain analgesics increase the risk of hypoglycaemia in elderly hypertensive and diabetic fracture patients which might be a combinatory effect of analgesics, anti-hypertensive, and/or anti-diabetic agents. Keywords: Hypoglycaemia; analgesics; bone fracture.